The guilty adjustment: Response trends on the symptom validity test - Shaw, Dominic J. (Legal and criminological psychology, 2014)
Purpose To our knowledge this was the first experiment that examined response trends over the course of a Symptom Validity Test (SVT). We predicted that the guilty group would avoid being associated with potentially incriminating information, and that they would do this more at the beginning of the test than towards the end. Method The 86 participants of the guilty group carried out an illegal activity in a room and were instructed to deny having been in that room in a subsequent interview. The 82 innocent participants had never been in that particular room. During the interview the guilty and innocent groups were exposed to a 12-item SVT. Results and Conclusion As predicted, the guilty participants selected fewer correct (crime related) items than innocents, and this tendency to avoid selecting the correct items was the strongest during the first half of the SVT. The implications of the findings for using an SVT in real life are discussed.